Pre-hispanic funerary architecture in cerro Calvario, Calca—Cusco - Camala Lizaraso, Franklin (2021)
The pre-Hispanic funerary architecture in the Calvario hill, province of Calca, Cusco, reveals a social organization, by the architectural attributes that present the funerary structures; form of plant, body, cover, size, materials, construction techniques, finishes and decorations. A total of 182 structures were recorded, located in cliffs, crevices and crags, with different types of groupings, with up to 8 levels of construction. These architectural attributes show similarities and variations to nearby sites in the Sacred Valley of the Incas.